A Liquid-Metal-Based Freestanding Triboelectric Generator for Low-Frequency and Multidirectional Vibration - Deng, Huaxia; Zhao, Zizheng; Jiao, Chong; Ye, Jingchang; Zhao, Shiyu; Ma, Mengchao; Zhong, Xiang (Frontiers in Materials, 2021)
There are a lot of vibration energy which are low-frequency, multi-directional and broadband in the nature. This creates difficulties for devices that aim at harvesting vibration energy. Here, we present a liquid-metal-based freestanding triboelectric generator(LM-FTG) for vibration energy harvesting. In this device, the fluidity of liquid is used to increase sensitivity to vibration for better low-frequency response and multi-directional vibration energy harvesting capability. The freestanding power generation mode is able to increase power generation stability. Experiments show that the bandwidth of LM-FTG can almost cover the entire sweep frequency range, and a 10µF capacitor can be charged to 6.46V at 7.5Hz in the 60s by LM-FTG. In particular, 100LEDs are illuminated in the low-frequency environmental experiment successfully. The proposed LM-FTG can work in low frequency with large working bandwidth, which provides an effective method for energy harvesting of low-frequency and multi-directional vibrations.